Gender Role in Global Personal Self-Esteem and Narcissism among Nepalese School Adolescents - Neupane, Dasarath; Timsina, Tatwa (Journal of Advanced Academic Research, 2017)
Introduction: Global personal self-esteem and narcissism with reference to gender role among school adolescents was studied in Kathmandu. The general aim of this research was to explore the correlation in global personal self-esteem and narcissism with response to gender among Nepalese school adolescents. Methodology: The study was correlational in design employing a pen-and-paper self-report survey. Within the survey, instruments (Rosenberg Self-Esteem Scale 1979 / RSES and Narcissistic Personality Inventory 1981/ NPI) measured the global personal self-esteem and narcissism. Participants were drawn from thirty (fifteen public and fifteen private) schools of Kathmandu. These schools were chosen in random selection. The number of participations was 936 school students. Results: The study investigated the prevalence of global personal self-esteem in the school with reference to gender. The result from the survey indicates that there is no significant difference between self-esteem and gender. On the other hand, girls are reported slightly higher narcissistic behaviour than boys. Conclusion: Self-esteem is how people feel about themselves generally. This study explored the prevalence rates of global personal self-esteem with reference to gender. It showed that there is no significant correlation between them. On the other hand, narcissism is a psychological condition defined as a total obsession with self, to the exclusion of almost all other interaction with people. The present study explored the prevalence rates of narcissism with reference to gender. It showed that girls reported slightly higher narcissistic behaviour than boys’ which contradicts the previous findings. Why it is found so in the Nepalese context is left for further research.